Product Quality, Brand Image and Pricing to Improve Satisfaction Impact on Customer Loyalty - Khoironi, Tubagus Agus; Syah, Hidayat; Dongoran, Parlindungan (International Review of Management and Marketing, 2018)
The purpose of this study is to know and analyze the influence of product quality, brand image, and price partially or simultaneously to customer satisfaction customer loyalty. The population of this research is the UMKM customer of EmpingMelinjo Industrial Sector in Banten Province.The research method used in this research is descriptive survey method and explanatory survey with sample size of 255 respondents, and data analysis method used is SEM (Structural Equation Modeling).Based on result of research, that product quality, brand image, and price partially or simultaneously have positive and significant effect of customer satisfaction with contribution equal to 53% and equal to 47% influenced by other variable not examined. Partially product quality is the most dominant variable affecting customer satisfaction. Product quality, brand image, price, and customer satisfaction partially or jointly have a positive and significant effect on customer loyalty with contribution of 84% and 16% influenced by other variable not examined. Partial customer satisfaction is the most dominant variable affecting customer loyalty. The result of research also shows that customer satisfaction is partial intervening variable on the influence of product quality, brand image, and price to customer loyalty. Keywords: Product Quality, Brand Image, Price, Customer Satisfaction, Customer Loyalty. JEL Classifications: M10, M21, M31